Improving Students' Learning Outcomes through the Application of Demonstration Method in Social Studies for Grade IV at SDN Gegeneng - Faradilla, Faradilla; Mutmainnatul Qolbiy, Iin; Salsabila, Syifa (LPPM Universitas Primagraha, 2023)
Based on the pre-research results of the implementation of social studies learning (1) learning activities are still dominated by teachers so that students are less active in learning (2) the method used in social studies learning is the lecture method, where the information/concepts being studied are notified or presented by the method. lecture only; (3) in the learning process the teacher does not provide reinforcement in the form of providing motivation to students. The problem formulation in this study is